A circular ecosystem for the implementation of sustainable development goals based on extended producer responsibility - Zybareva, Oksana V.; Verbivska, Liudmyla (My University, 2024)
Effective waste management is key to ensuring sustainable development in Ukraine. This study aims to explore the role of extended producer responsibility (EPR) and the circular economy in the implementation of sustainable development goals.This paper provides a comprehensive assessment of the responsible waste management sector in Ukraine. Negative trends such as an increase in waste volume, a decrease in productivity, and a failure to achieve target recycling and disposal levels were identified. This indicates the need for systemic transformations in waste management.The authors demonstrated that the implementation of EPR and circular economy principles is of key importance for overcoming the identified problems. EPR will encourage manufacturers to eco-design products and develop waste recycling infrastructure. The implementation of the circular economy concept requires a comprehensive approach that includes clear legislative regulation, developed infrastructure, financial and nonfinancial incentives, public awareness campaigns, and the integration of the formal and informal waste management sectors.Recommendations are given for the introduction of an effective EPR system, the development of waste recycling infrastructure, ensuring the coherence of legislation and policies, activating the involvement of all stakeholders, and developing scientific research and innovations in the field of the circular economy. The implementation of these measures will contribute to Ukraine's transition to a sustainable circular economy model and strengthen its contribution to the achievement of sustainable development goals.The scientific novelty of the study lies in the development of a methodological framework for a comprehensive assessment of the responsible waste management sector, the identification of key trends in the implementation of sustainable development goals, and the modeling of the equilibrium network interaction of the circular ecosystem. Prospects for further research relate to deepening the study of EPR mechanisms, the specifics of circular economy implementation, and the assessment of its effects.
Keywords: extended producer responsibility, circular economy, sustainable development, waste management, Ukraine